(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article reveals the peculiarities of development of students’ critical thinking in the process of studying works of art, gives definitions of the concept of "critical thinking" put forward by famous psychologists, characterizes the system of work on the analysis of the work, in the process of which students develop the ability to critically evaluate literary heroes.